The influence of parenting patterns on adolescent sexual behavior - Andri Nur Sholihah (Universitas 'Aisyiyah Yogyakarta, 2019)
The relationship between parenting and sexual behavior in adolescents is the main topic of this study. The research employeddescriptive correlation research method with cross sectional time approach. Respondents consisted of 80 adolescents and the sampling techniques used wastotal sampling techniques. Data were collected by using questionnaires and analyzed by using univariateanalysis, and bivariate analysis with chi square test. The results of the study showed that democratic parenting was 67,5%, permissive parenting was 11,25%,authoritarian parenting was 7,5% and for the application of mixed parenting was 13,75%. The correlation test results obtained p 0,05 (P=0,00) and coefficient value of 0,628 which means that there is a significant relationship and close relationship between parenting and adolescents sexual behavior.